Nghị quyết Bầu Tổng Kiểm toán Nhà nước nhiệm kỳ 2016 - 2021 (Nghị quyết số: 153/2021/QH14) - Quốc hội (2021)
Toàn văn Nghị quyết Bầu Tổng Kiểm toán Nhà nước nhiệm kỳ 2016 - 2021 (Nghị quyết số: 153/2021/QH14)